Executive functions in children with dyslexia - Barbosa, Thais; Rodrigues, Camila Cruz; Mello, Claudia Berlim de; Silva, Mariana Cristina de Souza e; Bueno, Orlando Francisco Amodeo (Arquivos de Neuro-Psiquiatria, 2019)
This study aimed to verify whether children with dyslexia have difficulties in executive functions (shifting, working memory, inhibition).Methods: A sample of 47 children (ages 8-13 years) participated in the study: 24 who were dyslexic and 23 controls with typical development. A battery of neuropsychological tests was used.Results: Results revealed executive function difficulties among the dyslexic children when compared with controls, encompassing selective attention modulation processes, shifting, and inhibitory control. These difficulties appeared to be affected by phonological working memory deficits, typically associated with dyslexia.Conclusion: Our findings support the consensus among scholars regarding the central involvement of phonological skill dysfunctions in dyslexia.
Keywords: Dyslexia; executive function; child; cognition